Case Report: Novel rare mutation c.6353C > G in the ABCA12 gene causing harlequin ichthyosis identified by whole exome sequencing - Tran, Van Khanh; Diep, Quang Minh; Zilong, Qiu; Phuong, Le Thi; Tran, Hai Anh; Van Tung, Nguyen; Lien, Nguyen Thi Kim; Xuan, Nguyen Thi; Ha, Le Thi; Van Ta, Thanh; Tran, Thinh Huy; Hoang, Nguyen Huy (Frontiers in Pediatrics, 2023)
Abstract Background: Harlequin ichthyosis (HI) is a severe rare genetic disease that mainly affects the skin. Neonates with this disease are born with thick skin and large diamond-shaped plates covering most of their bodies. They lose the ability to control dehydration and regulate temperature and are more susceptible to infection. They also face respiratory failure, and feeding problems and these are factors associated with high mortality rates of neonates with HI. Until now, there are still no effective treatments for HI patients and most patients die in the newborn period. The mutation of the ABCA12 gene, which encodes an adenosine triphosphate-binding cassette (ABC) transporter, has been demonstrated as the major cause of HI. Case presentation: In this study, we report the case who is one infant that was born prematurely at 32 gestational weeks with the whole body covered with thick plate-like scales of skin. The infant was severely infected with mild edema, multiple cracked skins full of the boy, yellow discharge, and necrosis of fingers and toes. The infant was suspected to be affected by HI. We performed whole exome sequencing (WES) as a tool for detecting the novel mutation in the patient. And after that, the mutation was confirmed by the Sanger sequencing method in the patient and the members of his family. In this case, one novel mutation, c.6353C>G (p.S2118X, Hom) in the ABCA12 gene, was detected in one prematurely born Vietnam infant with HI phenotype. The mutation has not been reported in any HI patients previously. This mutation was also found in a heterozygous state in the members of the patient’s family, including his parents, an older brother, and an older sister who are no symptoms. Conclusions: In this study, we identified a novel mutation in a Vietnamese patient with HI by whole exome sequencing. The results for the patient and the members of his family will be helpful in understanding the etiology of the disease, diagnosing carriers, assisting in genetic counseling, and emphasizing the need for prenatal screening for families with a history of the disease.